PROBLEMS OF CLASSIFICATION OF TYPES OF ARGUMENTATION (Web of Teachers: Inderscience Research, 2024)
Argumentation is a complex intellectual activity aimed at conveying a specific thought, substantiating an idea, point of view, theoretical position, hypothesis or concept. Argumentation in scientific (and philosophical) activity is associated with a comprehensive consideration of the problem under study and involves bringing specific grounds for any expressed thought, including summing up the philosophical foundations of the proposed scientific theory or philosophical concept. its individual provisions.